: Utilization of GPS data in the effort of Mineral Identification in Granite Rocks Using X-Ray Diffraction in Samadua District, South Aceh - Bakruddin D; Safridatul Audah (Jurnal Inotera, 2019)
South Aceh has abundant natural resources, one of which is granite rock, at Kutablang Village and Lubuk Layu Village, Samadua District. This research discusses about minerals phases using the X-Ray Diffraction method. The results obtained in the phase of the granite constituent minerals from Kutablang Village were C16AlClN16S4, O2Si, and F15Mo5O15Rb15, and the phases of the constituent minerals from Lubuk Layu Village were O2Si, F15Mo5O15Rb15 and La2Mo2O9.